MOLECULAR MARKERS OF SENSITIVITY AND RESISTANCE OF COLORECTAL CANCER TO ANTI-EGFR T - A. O. Ivantsov; G. A. Yanus; E. N. Suspitsin; E. I. Anisimova; E. N. Imyanitov (Сибирский онкологический журнал, 2016)
Targeted therapy of metastatic colorectal cancer lacks predictive markers with positive predictive value, i.e. the selection of potentially responsive patients remains highly complicated. In contrast, there are very reliable markers indicating resistance to the therapy by anti-EGFR antibodies. Assessment of such markers is mandatory when EGFR targeting is considered. An analysis of tumor DNA for mutations in coding regions of KRAS and NRAS genes has become a standard procedure; the occurrence of these mutations is within 45-65%. Nevertheless, exclusion of KRAS/NRAS-mutated cases remains insufficient for the reliable selection of potential responders. There is a continuing search for novel predictive biomarkers. Multiple evidences support the role of BRAF V600E mutation in determining non-response to anti-EGFR therapy. Some data suggest an impact of PIK3CA, PTEN, EREG, AREG, IGF2 mutations and/or expression changes, as well as the significance of MET and HER2/neu gene amplifications. Further progress in this field is expected to improve clinical and economic efficacy of colorectal cancer treatment.